From protest to challenge: A documentary of African politics in South Africa, 1882-1990. Volume 4, Political Profiles 1882-1990 (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This book is the fourth volume in a series covering African politics in South Africa from 1882 to 1990. It presents the work done by 571 carefully-selected individuals that were critical in forging a way to emancipate African society from colonial and apartheid oppression. The culmination of the profiles of each of these individuals is how they contributed immensely to the making of present-day South Africa.